Sugar synthesis in a protocellular model leads to a cell signalling response in bacteria - Gardner, P; Winzer, K; Davis, B (Macmillan Publishers Ltd., 2009)
The design of systems with life-like properties from simple chemical components may offer insights into biological processes, with the ultimate goal of creating an artificial chemical cell that would be considered to be alive. Most efforts to create artificial cells have concentrated on systems based on complex natural molecules such as DNA and RNA. Here we have constructed a lipid-bound protometabolism that synthesizes complex carbohydrates from simple feedstocks, which are capable of engaging the natural quorum sensing mechanism of the marine bacterium Vibrio harveyi and stimulating a proportional bioluminescent response. This encapsulated system may represent the first step towards the realization of a cellular 'mimic' and a starting point for 'bottom-up' designs of other chemical cells, which could perhaps display complex behaviours such as communication with natural cells.